Social Media Integration in the Jigsaw Model: Innovative Solutions to Improve Students' Communication Skills - Ngatmini, Ngatmini; Muhajir, Muhajir; Rozzaqi, Ade Ricky (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to analyze the effectiveness of the social media-based jigsaw learning model in improving the communication skills of students of the Indonesian Language and Literature Education Study Program (PBSI) Universitas PGRI Semarang. The method used is an experiment with the design of prates and posts. The experimental group received learning using a jigsaw model integrated with social media, while the control group was taught conventionally. Data were obtained through tests of communication skills, observations, and interviews, which were analyzed descriptively, quantitatively, and qualitatively. The results of the study showed a significant increase in students' communication skills. The average score increased from 65 on prates to 86 on posts. The distribution of scores also shifted drastically, from the majority in the low category (60–65) to dominant in the high category (80–90). This increase is associated with the active role of students in group discussions as well as increased comfort and access to information through social media. The jigsaw model facilitates meaningful collaborative interactions, while social media flexibly expands the discussion space. This technology-based learning has proven to be effective in building essential communication skills for aspiring educators. However, the implementation of this model still requires strict supervision so that the use of social media remains focused on academic goals. This research contributes to the development of innovative learning strategies in the digital age, and opens up opportunities for further exploration in other educational contexts.